Aligning practitioner's perception: Empowering MAST framework for evaluating telemedicine services - Ayesha Parvez; Javeria Saleem; Muhammad Ajmal Bhatti; Arshad Hasan; Asif Mahmood; Zulfiqar Ali; Tauseef Tauqeer (Digital Health)
Objective Telemedicine is a digital substitute for in-person healthcare service delivery systems that has gained popularity amid the global COVID-19 pandemic. The objective of this study was to evaluate telemedicine compatibility from the perspective of healthcare practitioners to enhance the effectiveness and spectrum of the Model for Assessment of Telemedicine. Method Primary and Secondary Healthcare and King Edward Medical University extended their respective telemedicine services in 2020 where 24,516 patients were benefited from the telemedicine services provided by 1273 doctors from different specializations. A cross-sectional survey via online questionnaire was conducted among purposively sampled 248 healthcare practitioners designated at telemedicine portals in the public sector; further analysed by descriptive analysis and Monte Carlo Feature Selection. Results Healthcare practitioner perception was analysed explicitly and found significant in addition to the existing domains under multidisciplinary assessment in the Model for Assessment of Telemedicine model. The variables of subdomains integration with healthcare system, patient facilitation, technology ease, capacity building, ethical integrity, outcome assessment and communication gap under proposed healthcare practitioner perception domain were found interdependent. The variables of patient satisfaction, resource preservation, healthcare practitioner satisfaction, digital connectivity, user-friendliness, and patient safety were found to be of higher importance (RI values). However, the compatibility of telemedicine with the healthcare system was also influenced by interdependencies (RI plot) and multifaceted interactions of variables derived from the healthcare practitioner perception. Conclusion The variables of healthcare practitioner perception were exhibiting various weightages of importance and interdependencies in determining the compatibility of telemedicine within the healthcare system and recommended to be considered in the Model for Assessment of Telemedicine framework.